2018
DOI: 10.3892/ol.2018.8048
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑26a regulates ANXA1, rather than DAL‑1, in the development of lung cancer

Abstract: Abstract. The aim of the present study was to investigate the expression and role of microRNA-26a (miR-26a) in lung cancer, and to verify whether differentially expressed in adenocarcinoma of the lung (DAL-1) is the target protein of miR-26a. mRNA expression levels of miR-26a and DAL-1 were detected using reverse transcription-quantitative polymerase chain reaction. Protein expression levels of DAL-1 and annexin A1 (ANXA1) were evaluated by western blot analysis. Cell Counting Kit-8, Transwell and wound scratc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Data from several studies previously showed that miR-223 does not only promote the invasion of lung cancer cells but also the metastasis of gastric cancer via targeting tumor suppressor DAL-1 (8,9). Our previous study demonstrated that both miR-26a and DAL-1 gene expression are decreased in NSCLC, and DAL-1 is not a real target gene of miR-26a (10). Both miR-26b and miR-26a belong to the miR-26 family, and miR-26b has low expression levels in many types of cancer, such as epithelial ovarian (EOC) (11), hepatocellular carcinoma (HCC) (12), as well as colorectal cancer (13).…”
Section: Introductionmentioning
confidence: 94%
“…Data from several studies previously showed that miR-223 does not only promote the invasion of lung cancer cells but also the metastasis of gastric cancer via targeting tumor suppressor DAL-1 (8,9). Our previous study demonstrated that both miR-26a and DAL-1 gene expression are decreased in NSCLC, and DAL-1 is not a real target gene of miR-26a (10). Both miR-26b and miR-26a belong to the miR-26 family, and miR-26b has low expression levels in many types of cancer, such as epithelial ovarian (EOC) (11), hepatocellular carcinoma (HCC) (12), as well as colorectal cancer (13).…”
Section: Introductionmentioning
confidence: 94%
“…27 ANXA1 was dysregulated in various diseases, highlighting its significant function in tumor progression. 28 ANXA1 expression could be quite different in cancers, and the opposite expression of ANXA1 is the only one of the mysteries of B, Western blot analysis of related protein expression in each group; *P < 0.05 vs the blank group; measurement data were expressed as mean ± standard deviation, data of multiple group data were compared using one-way ANOVA, and the experiment was repeated three times. ANOVA, analysis of variance; miR, microRNA its potential regulatory mechanisms and phenotypic specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of ANXA1 detected in different cancers are not consistent. In certain tumors such as head and neck, esophageal squamous cell and prostate cancers they are down regulated and in others like glioma and oropharngeal cancers they are up regulated 6…”
Section: Introductionmentioning
confidence: 99%
“…In certain tumors such as head and neck, esophageal squamous cell and prostate cancers they are down regulated and in others like glioma and oropharngeal cancers they are up regulated. 6 Pakistan is a multiethnic state with five provinces and different ethnicities. This study was aimed to assess the risk association of miR-196a rs11614913 C/T variant and the relationship of miR-196a genotype with expression of its target gene ANXA1 in BC cases.…”
Section: Introductionmentioning
confidence: 99%